La afectación del sistema sensorial en niños con autismo en la primera infancia de 6 años - Baldeón Morán, Doménica Gabriela (2023)
The purpose of this paper is to analyze the influence of the development of the sensory system in children with autism in the development of their daily activities, so the methodology implemented is qualitative due to its flexibility in the deepening of the data obtained, using an observation sheet with indicators aimed at identifying the sensory stimuli to which 5 children with Autism Spectrum Disorder (ASD) mostly responded. And also applied different interviews to 2 teachers, 5 parents and an expert in the subject. Finally, these resulted in sensory development in children with ASD is one of the fundamental bases for the development of their learning and other skills and if not intervened in time the difficulties that these people have will persist throughout their lives preventing not only a full learning, but It would also affect the development of social skills, their interaction with the environment around them and their own autonomy.